COPYRIGHT AND MARKET DOMINANCE IN ARTIFICIAL INTELLIGENCE PLATFORMS: CHALLENGES OF PROTECTING COMPETITION IN THE CONTEXT OF BIG TECH - Hazratqulova , Sevinchbeka (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
This thesis analyzes the relationship between copyright and competition law in the context of artificial intelligence platforms. Modern AI systems rely on large datasets, often involving copyrighted content, which raises significant legal concerns. The research examines the market dominance of Big Tech companies, their privileged access to data, and the resulting impact on competition. It also develops recommendations based on international practices to balance copyright protection and fair competition in AI markets.